Sleep deprivation affects sensorimotor coupling in postural control of young adults - Aguiar, Stefane A.; Barela, Jose A. [UNESP] (Elsevier B.V., 2014)
Although impairments in postural control have been reported due to sleep deprivation, the mechanisms underlying such performance decrements still need to be uncovered. The purpose of this study was to investigate the effects of sleep deprivation on the relationship between visual information and body sway in young adults' postural control. Thirty adults who remained awake during one night and 30 adults who slept normally the night before the experiment participated in this study. The moving room paradigm was utilized, manipulating visual information through the movement of a room while the floor remained motionless. Subjects stood upright inside of a moving room during four 60-s trials. In the first trial the room was kept stationary and in the following trials the room moved with a frequency of 0.2 Hz, peak velocity of 0.6 cm/s and 0.9 cm peak-to-peak amplitude. Body sway and room displacement were measured through infrared markers. Results showed larger and faster body sway in sleep deprived subjects with and without visual manipulation. The magnitude with which visual stimulus influenced body sway and its temporal relationship were unaltered in sleep deprived individuals, but they became less coherent and more variable as they had to maintain upright stance during trials. These results indicate that after sleep deprivation adults become less stable and accurate in relating visual information to motor action, and this effect is observed after only a brief period performing postural tasks. The low cognitive load employed in this task suggests that attentional difficulties are not the only factor leading to sensorimotor coupling impairments observed following sleep deprivation. (C) 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: Sleepiness; Postural sway; Sensorimotor coupling; Attention; Visual information